2007
DOI: 10.1002/mrm.21352
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine‐19 MRI for visualization and quantification of cell migration in a diabetes model

Abstract: This article describes an in vivo imaging method for visualizing and quantifying a specific cell population. Cells are labeled ex vivo with a perfluoropolyether nanoparticle tracer agent and then detected in vivo using 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
500
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 241 publications
(510 citation statements)
references
References 37 publications
7
500
3
Order By: Relevance
“…Quantitation of the number of cells based on 19 F signal was performed similar to the previously published algorithm. 27 Briefly, low-SNR magnitude image voxels were corrected for their Rician distribution by generating a lookup table between measured and expected signal intensity. Using a region-of-interest (ROI) drawn in the noise/background, the standard deviation of either the real or imaginary signal of the complex 19 F MR data was calculated (s N ) on a per-slice basis.…”
Section: Quantitative Analysis Of 19 F Signal In Vivomentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitation of the number of cells based on 19 F signal was performed similar to the previously published algorithm. 27 Briefly, low-SNR magnitude image voxels were corrected for their Rician distribution by generating a lookup table between measured and expected signal intensity. Using a region-of-interest (ROI) drawn in the noise/background, the standard deviation of either the real or imaginary signal of the complex 19 F MR data was calculated (s N ) on a per-slice basis.…”
Section: Quantitative Analysis Of 19 F Signal In Vivomentioning
confidence: 99%
“…14 The same group has subsequently employed 19 F-MRI to track and quantify: autoreactive mouse T cells, 27 antigen specific T cells, 28 monocyte and macrophages in two rat models of renal and cardiac allograft rejection, 24 and PFPE-labeled human primary DCs in immunodeficient mice. 25,26 Other investigators have also reported on the ability to ex vivo label other potential cell therapies with 19 F, including murine 30 and human neural stem cells, 31 human CD34 C hematopoietic stem cells (HSCs) and mouse bone marrow derived HSCs as well as murine 32 and human 33 19 F-MRI without apparent toxicity.…”
mentioning
confidence: 99%
“…Cell product release criteria included thresholds for bacterial contamination, the presence of endotoxins, and cell viability. Nuclear magnetic resonance (NMR) was used to assay the 19 F content of the DCs after PFC labeling (4,6). Briefly, cell pellets containing a known cell number ($3 Â 10 6 ) were lysed with 1% Triton X-100 (Arcos Organics), and 0.1% (v/v) trifluoroacetic acid (TFA, Sigma-Aldrich, St Louis, MO) was added as an NMR reference compound.…”
Section: Preparation and Pfc Labelingmentioning
confidence: 99%
“…19 F SI was measured directly from axial slice of HFB device [11]. The changes in 19 F SI at different H8-H21 concentrations were observed and the calibration curves were prepared, as 19 F SI is linearly related with the amount of 19 F molecules [12].…”
Section: Calibration Curvementioning
confidence: 99%